Characterization of novel Wnt/β-catenin pathway targets - Akiva, İzzet. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
The Wnt/β-catenin signaling pathway is an evolutionary conserved pathway which has important functions in vertebrate early development such as axis formation, cellular proliferation and morphogenesis. The activation of this pathway leads to translocation of the transcriptional activator β-catenin into the nucleus where it activates T-cell factor/Lymphoid enhancer factor (Tcf/Lef) family of transcription factors, which regulate expression of developmental and cell cycle-related genes. Apart from its roles in various cellular processes, Wnt/β-catenin signaling pathway is also one of the most important intracellular pathways implicated cancer progression. A significant number of identified target molecules of this pathway, are known to have tumorigenic characters when mutated. Previous studies confirmed BRI3 (Brain protein I3) gene to be one of the transcriptional target genes of Wnt/β-catenin pathway. We used various approaches for the functional characterization of its novel targets. As a first step in our study, IFITM3 and MGAT1 proteins were confirmed as interaction partners for BRI3 by Yeast-two Hybrid and Co-IP techniques. BRI3 was found to be upregulated in response to TNF-α treatment and overexpression of BRI3 resulted in an increase in NFkB promoter activity. On the other hand, MGAT1 is a putative novel target of Wnt/β-catenin signaling pathway and determined to be upregulated in response to β-catenin activation. Cell proliferation and migration assays showed that, Huh7 cells stably expressing each of the BRI3 and MGAT1 genes have greater proliferative and invasive capabilities compared to control Huh7 cells. Furthermore, in vivo xenograft experiments were performed and it was determined that the stable overexpression of both of these genes in Huh7 cell lines lead to increased rate of tumor growth in NUDE/SCID mice. The resulting tumors were subjected to transcriptomic analyses using RNA-Sequencing technique in order to determine which pathways and biological processes take part in the cancer initiation process.
Keywords: Catenins -- Mechanism of action.; Wnt genes.